ДВОНАПРАВЛЕНИЙ КАСКАДНИЙ ПЕРЕТВОРЮВАЧ ПОСТІЙНОЇ НАПРУГИ ДЛЯ ПОТУЖНОЇ СИСТЕМИ ЕНЕРГОНАКОПИЧЕННЯ В МЕРЕЖАХ ЕЛЕКТРОПОСТАЧАННЯ SMART GRID - Руденко, Ю.В.; Мартинов, В.В. (Інститут електродинаміки Національної академії наук України, 2023)
Electromagnetic processes in a bidirectional cascade DC converter with the possibility of increasing and decreasing the output voltage levels in both directions of energy transfer for electric power storage systems are considered. Using the method of averaging in the state space, a mathematical model of the pulse converter was obtained. Analytical expressions for calculating the ripple characteristics of a bidirectional cascade converter have been determined, with the help of which you can calculate the main parameters of the constant voltage converter, which provide permissible voltage ripples on the DC buses and power choke current. To illustrate the developed calculation methodology, the ripple characteristics and parameters of a 30 kW converter for various load modes with 400V and 700V DC busbars for use in energy storage systems are determined. The bidirectional converter was calculated, analyzed and simulated in Mathcad/PSim packages at idle speed and at different load levels in order to confirm the effectiveness of the conducted research. Ref. 7, fig. 2.